Uterine Microbiota of Dairy Cows With Clinical and Subclinical Endometritis - Wang, Meng-Ling; Liu, Ming-Chao; Xu, Jin; An, Li-Gang; Wang, Jiu-Feng; Zhu, Yao-Hong (Frontiers in Microbiology, 2018)
The objective of this study was to characterize the uterine microbiota of dairy cows with clinical and subclinical endometritis and to identify the potential bacterial genera as well as their interactions associated with uterine disease. Uterine flush samples (n = 27) were collected from 13 healthy, 5 subclinical endometritic (SE), and 9 clinical endometritic (CE) cows at 30 days postpartum. Microbial DNA from uterine flush samples was subjected to sequencing of the 16S rRNA gene on the Illumina MiSeq platform. The uterine microbiota of healthy, SE, and CE cows had similarly complex microbial diversity, and shared 293 of 445 operational taxonomic units. However, endometritic and healthy cows could be discriminated by the relative abundance of bacterial genera. In CE cows, the uterine microbiota was characterized by increased abundance of Fusobacterium and unique presence of Trueperella and Peptoniphilus. For SE cows, known intrauterine pathogens were almost absent and the uterine microbiota was characterized by enrichment of Lactobacillus and Acinetobacter. Analysis of correlations between bacterial genera showed that the uterine microbiota exhibited two co-occurrence groups (i.e., the Lactococcus and the Fusobacterium COGs), indicating that the synergistic effect by co-occurred bacteria may be an important aspect of pathogenesis. Our findings support that common uterine pathogens are not associated with subclinical endometritis at 30 days postpartum and indicate the need of investigating the role of commensal bacteria such as Lactobacillus, and Acinetobacter in the inflammatory process of uterine endometrium.